Pengaruh Lingkungan Sosial dan Pengendalian Diri Terhadap Perilaku Keuangan: Studi Kasus Mahasiswa Manajemen UBP Karawang Angkatan 2021 - Iis Rahayu; Ujang Suherman; Rengga Madya Pranata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of social environment and self-control on the financial behavior of students in the Management Study Program at Universitas Buana Perjuangan Karawang, Class of 2021. This research uses a descriptive quantitative approach. The population in this study consists of 412 students, with a sample size of 80 students selected using simple random sampling technique. Data was collected through an online questionnaire and analyzed using validity tests, reliability tests, classical assumption tests, and regression analysis.The results of the study show that the social environment significantly influences students' financial behavior. A positive social environment, such as support from family, peers, and the educational environment, shapes better financial habits. Students who are accustomed to being in an environment that provides examples of wise financial management tend to imitate these patterns in their daily lives. Additionally, self-control was also found to have a significant impact on students' financial behavior. Students with a high level of self-control are able to resist the urge to make impulsive purchases, manage their spending more systematically, and remain consistent in achieving long-term financial goals.Simultaneously, both of these variables contribute to students' financial behavior, with an R Square value of 0.679. This means that 67.9% of the variability in financial behavior can be explained by the social environment and self-control, while the remaining variance is influenced by factors outside the scope of this research model.